Radiative thermal criticality and entropy generation of hydromagnetic reactive Powell-Eyring fluid in saturated porous media with variable conductivity - S. O. Salawu; R. A. Kareem; S. A. Shonola (Energy Reports, 2019)
Theoretical study of inherent irreversibility and thermal runaway of an exothermic reactive Eyring-Powell fluid flow through a saturated porous fixed horizontal channel with thermal radiation and variable electrical conductivity is investigated. The reactive conducting fluid under bimolecular chemical rate law is propelled by pressure gradient. Ignoring the material assumptions, the governing dimensionless equations of the flow model are solved using semi discretization finite difference techniques coupled with weighted residual method. The results in terms of flow rate, temperature, thermal runaway, Bejan number and entropy generation are presented in graphical form. From the results, it is observed that parameter which argument the entropy production rate also enhances the Bejan number. Also, minimization of entropy generation is achieved at low values of thermal radiation, dissipation rate, electric field loading and viscosity variables.
Keywords: 330; Inherent irreversibility; Non-Newtonian; Reactive fluid; Thermal radiation; Thermal runaway